Central neuropathic pain in MS is due to distinct thoracic spinal cord lesions. (28th July 2014) - Okuda, Darin T.; Melmed, Kara; Matsuwaki, Takashi; Blomqvist, Anders; Craig, Arthur D. Bud
Abstract Objective To determine a neuro‐anatomic cause for central neuropathic pain (CNP) observed in multiple sclerosis (MS) patients. Methods Parallel clinical and neuro‐anatomical studies were performed. A clinical investigation of consecutively acquired MS patients with and without CNP (i.e. cold allodynia or deep hyperesthesia) within a single MS center was pursued. A multivariate logistic regression model was used to assess the relationship between an upper central thoracic spinal cord focus to central pain complaints. To identify the hypothesized autonomic interneurons with bilateral descending projections to lumbosacral sensory neurons, retrograde single‐ and double‐labeling experiments with CTb and fluorescent tracers were performed in three animal species (i.e. rat, cat, and monkey). Results Clinical data were available in MS patients with (n = 32; F:23; median age: 34.6 years (interquartile range [IQR]: 27.4–45.5)) and without (n = 30; F:22; median age: 36.6 years [IQR: 31.6–47.1]) CNP. The value of a central focus between T1–T6 in relation to CNP demonstrated a sensitivity of 96.9% (95% confidence interval [CI]: 83.8–99.9) and specificity of 83.3% (95% CI: 65.3–94.4). A significant relationship between CNP and a centrally located focus within the thoracic spine was also observed (odds ratio [OR]: 155.0 [95% CI lower limit: 16.0]; P < 0.0001, two‐tailed Fisher exact test). In all animal models, neurons with bilateral descending projections to the lumbosacral superficial dorsal horn were concentrated in the autonomic intermediomedial nucleus surrounding the mid‐thoracic central canal. Interpretation Our observations provide the first evidence for the etiology of CNP. These data may assist with the development of refined symptomatic therapies and allow for insights into unique pain syndromes observed in other demyelinating subtypes.